3D vs. 2D simulated fetoscopy for spina bifida repair: a quantitative motion analysis - Mirza Awais Ahmad; Yolan Weiler; Luc Joyeux; Elisenda Eixarch; Tom Vercauteren; Sebastien Ourselin; Jan Deprest; Emmanuel Vander Poorten (Scientific Reports, 2023)
Abstract 3D imaging technology is becoming more prominent every day. However, more validation is needed to understand the actual benefit of 3D versus conventional 2D vision. This work quantitatively investigates whether experts benefit from 3D vision during minimally invasive fetoscopic spina bifida (fSB) repair. A superiority study was designed involving one expert team ( $$>18$$ > 18 procedures prior) who performed six 2D and six 3D fSB repair simulations in a high-fidelity animal training model, using 3-port access. The 6D motion of the instruments was recorded. Among the motion metrics are total path length, smoothness, maximum speed, the modified Spectral Arc Length (SPARC), and Log Dimensionless Jerk (LDLJ). The primary clinical outcome is operation time (power 90%, 5% significance) using Sealed Envelope Ltd. 2012. Secondary clinical outcomes are water tightness of the repair, CO $$_2$$ 2 insufflation volume, and OSATS score. Findings show that total path length and LDLJ are considerably different. Operation time during 3D vision was found to be significantly shorter compared to 2D vision ( $$113± 9$$ 113 ± 9 vs. $$149± 19$$ 149 ± 19 min; p $$=$$ = 0.026). These results suggest enhanced performance with 3D vision during interrupted suturing in fetoscopic SBA repair. To confirm these results, a larger-scale follow-up study involving multiple experts and novice surgeons is recommended.